Розробка математичної моделі просторового руху інструменту узагальненої схеми бурового виконавчого органу суцільного руйнування - Довгаль, Д. О. (My University, 2023)
The purpose of the work is to develop a mathematical model of the kinematics of the spatial motion of a single cutting tool of the generalized scheme of the executive unit of complete destruction. Methodology. The basis for the development of the basic generalized scheme of the kinematics of the cutting tool movement is the analytical synthesis of all existing constructive schemes of the drilling executive unit, the work of which is based on the transmission of one or more rotational movements to the tool simultaneously with the forward movement. Individual cases of structural schemes have been discovered by analyzing the possible positions of the working disk, as well as the number of movements transmitted to the cutting tool during its operation.
Development of a mathematical model of the spatial motion of the tool of the generalized scheme of a drilling executive unit of complete destruction
Keywords: буровий виконавчий орган; планетарний виконавчий орган; кінематика руху інструменту; моделювання руху різця; drilling executive unit; planetary executive unit; kinematics of tool movement; cutter movement simulation